Evaluating Digital Public Relations Strategies Of The Surakarta City Tourism Office In Promoting Sustainable Tourism - Haryo Kusumo Aji; Andika Drajat Murdani; Harbono (CV. RADJA PUBLIKA, 2025)
This study evaluates the digital public relations (PR) strategy of the Surakarta City Tourism Office in enhancing sustainable tourism communication through social media and digital promotional content. The research employs a qualitative descriptive approach with the CIPP (Context, Input, Process, and Product) evaluation model to assess the effectiveness, implementation, and impact of the city’s digital communication practices. Data were collected through in-depth interviews, observation, and documentation involving tourism officials, creative community members, and online audiences. The findings reveal that Surakarta has made significant progress in adopting digital communication to strengthen its city branding as a cultural and creative destination. However, the integration of sustainability messages—such as environmental awareness, cultural preservation, and community empowerment—remains limited. From the input perspective, human and technological resources are available but require capacity development and consistent strategic alignment. In terms of process, the digital PR activities focus mainly on event promotion and aesthetic storytelling, while participatory and educational content is less emphasized. At the product level, digital engagement has improved visibility and audience interaction but has not yet resulted in long-term sustainability awareness. The study concludes that Surakarta’s digital PR strategy is effective in enhancing destination image but less effective in embedding sustainability communication. Strengthening sustainability-driven storytelling, participatory collaboration, and digital capacity building is recommended to achieve more inclusive and responsible tourism communication. Theoretically, this research contributes to expanding the use of the CIPP evaluation model in the study of digital communication governance and sustainable destination management.